European Experience Features of Translation Theory and Practice Teaching of Future Foreign Philologists - Dolynskiy, Ievgen (Pedagogical Discourse, 2020)
The article analyzes the experience of professional training of future translators with the use of information and communication technologies in higher education institutions of the European Union. Requests from developed European countries form a new level of translation. Today, there is an extensive network of translation education in the world, which includes public universities, public and private schools and translation institutes, and courses. There are several basic models for training translators. Educational programs and qualification characteristics of graduates are adjusted according to the needs of the translation services market. 215 higher education institutions train translators in Europe. In Western European countries, the most common are the following qualification levels: «bachelor», «master», «doctor of philosophy». The student has the opportunity to create an individual package of courses. Getting quality education by future translators requires significant resources and contributions. Universities have a high level of logistics. The practical component of the programs has active and passive production practices. The training of future translators in universities is based on the principles of scientificity, continuity and continuity of education, taking into account the capabilities of modern information technology. Interactive information technologies that develop translators’ communication skills are common in British universities. In France, multidisciplinary translators, specialists in localization, terminology, legal translation, translators of official documents, etc. are currently being trained. Particular attention is now being paid to training translators in the use of SAT technologies. In Austria, translators are trained at three universities in the country. The effectiveness of measures to improve the quality of professional training of future translators in the information and educational environment of the university depends on the positive components of foreign experience.